Happy and resilient? Mental health, resilience, substance use and sexual behaviour of college students in Bhutan: Policy implications - Sherab, Kezang; Howard, J; Choden, K (Bhutan Journal of Research and Development, 2024)
Bhutan is known for its guiding philosophy of Gross National Happiness (GNH). However, concerns have increased about the well-being of its young people, and many young people are leaving Bhutan, uncertain about their futures if they remain. A survey of 2471 Bhutanese college students in 2016 explored mental health, substance use, and sexual behaviour. The survey was repeated in 2023 with 2043 college students with the addition of the Brief Resilience Scale and questions about optimism and the future. A relatively low prevalence of problematic mental health, substance use, and sexual risk behaviour was identified, but the findings continue to raise concerns. Specific concerns identified related to suicidal ideation, an increase in current alcohol, tobacco and betel nut use, low-level condom use, over 50% not regarding themselves as resilient, and many wanting a future outside Bhutan. Evidence informed policy is required to shape and support responses to the health and well-being concerns identified and to create realistic pathways for young people to feel valued, appreciated and optimistic.